(untitled) - Cuate, Melodie A. (Lubbock, 2012)
"Hannah, Nick, and Jackie time-travel to Texas in 1840. Taken captive by Comanche warriors, Hannah and Jackie experience Comanche life and participate in the Linnville raid; Nick meets Bigfoot Wallace and the Texas Rangers, who pursue the Comanche party until the two groups clash in the Battle of Plum Creek"--Provided by publisher.
Keywords: Wallace, Big-Foot; 1817-1899; Juvenile fiction; Wallace, Big-Foot; 1817-1899; Fiction; Texas Rangers; Fiction; Fiction; Time travel; Texas; Frontier and pioneer life; Fiction; Fiction; Texas; Fiction; Indians of North America; Fiction; Comanche Indians; Indian captivities; To 1846; History; Fiction; Texas; To 1846; Juvenile fiction; Texas; History